Development and implementation of information project management system in building companies - Кальніченко, Олена Володимирівна; Чернова, Марина Леонідівна (Technology audit and production reserves, 2015)
The article is devoted to research of a problematic field of management of complicated investment-building projects in project-oriented building companies. In the article are studied key issues that happen to Main Contractor organizations on the stages of preparation and realization of projects, and also possible technical realization of main goals, using applied specific program solutions on the base of modern information technologies. Were studied the possibilities to apply modern information project management systems to different types of the projects, that make a significant part of corporate project management system. On the example of the turn-key hotel building project were shown the results of development and implementation of additional and specific program modules on the base of project management information systems in investment-building projects. Suggested decisions made it possible to automatize the process of transition from commercial proposal development stage to detailed project planning. In its turn, the adoption of functional of existing program products to requirements of building industry peculiarities and unique demands of certain building company made it possible to extend the application of project management information systems and to improve their effectiveness.